A lung-inspired printed circuit board polymer electrolyte fuel cell. (15th December 2019) - Bethapudi, V.S.; Hack, J.; Trogadas, P.; Cho, J.I.S.; Rasha, L.; Hinds, G.; Shearing, P.R.; Brett, D.J.L.; Coppens, M.-O.
Highlights: Layer wise PCB based fractal lung-inspired cathode flow field. Cost effective and light weight method of fractal flow field development. Enhanced performance over serpentine flow field at a range of operating conditions. Uniform and sustained operation of fractal flow field with better water management. Abstract: Fractal cathode flow-fields, inspired by the flow mechanism of air inside lungs, can provide homogeneous, scalable and uniform distribution of reactants to polymer electrolyte fuel cell (PEFC) electrodes. However, the complex 3D flow-fields demonstrated previously face manufacturing challenges, such as requiring selective laser sintering, an additive manufacturing method that is expensive to scale up. Here, a lung-inspired cathode flow-field is introduced and fabricated using low-cost, lightweight printed circuit boards (PCB). The uniformity and alignment between individual PCB layers producing the fractal hierarchy of flow channels have been characterised using X-ray computed tomography (X-ray CT). The performance of the fractal flow-field exceeds that of conventional single-serpentine flow-fields and is particularly beneficial when operating on air with a low relative humidity. The lung-inspired design is shown to lead to a more stable operation than the single-serpentine design, as a result of uniform distribution of reactants.